The role of loneliness, sexual satisfaction and forgiveness in predicting depression in women affected by infidelity - Ebrahimi, Elham; Zargham Hajebi, Majid; Navabinejad, Shokoh (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to investigate the role of loneliness, sexual satisfaction, and forgiveness in predicting depression in women affected by infidelity. Methods: 250 women affected by infidelity in Tehran were selected usinghe purposive sampling method and participated in this study. Participants completed the Russell & Pilva & Cortona (1980) Loneliness Questionnaire, Larson et al. (1998), Ray et al. (2001), and Beck (1996) Depression Inventory. Data analysis was performed using Pearson correlation coefficient and multiple regression. Results: The findings showed that there was a significant negative relationship between feelings of loneliness and depression (P